Dopamine-Signaled Reward Predictions Generated by Competitive Excitation and Inhibition in a Spiking Neural Network Model - Chorley, Paul; Seth, Anil K. (Frontiers in Computational Neuroscience, 2011)
Dopaminergic neurons in the mammalian substantia nigra display characteristic phasic responses to stimuli which reliably predict the receipt of primary rewards. These responses have been suggested to encode reward prediction-errors similar to those used in reinforcement learning. Here, we propose a model of dopaminergic activity in which prediction error signals are generated by the joint action of short-latency excitation and long-latency inhibition, in a network undergoing dopaminergic neuromodulation of both spike-timing dependent synaptic plasticity and neuronal excitability. In contrast to previous models, sensitivity to recent events is maintained by the selective modification of specific striatal synapses, efferent to cortical neurons exhibiting stimulus-specific, temporally extended activity patterns. Our model shows, in the presence of significant background activity, (i) a shift in dopaminergic response from reward to reward predicting stimuli, (ii) preservation of a response to unexpected rewards, and (iii) a precisely-timed below-baseline dip in activity observed when expected rewards are omitted.